Innovation IT-Payment Technologies as a Know-how and an Object of Intellectual Property Rights - Gramatskyy, Ernest; Kryvosheyina, Inha; Makoda, Volodymyr; Panova, Liydmyla (Cuestiones Políticas, 2020)
The modern society necessitates the introduction of new IT-solutions to meet its needs. With the spread of know-how, the need for its detailed analysis with the further determination of the direction of development. The purpose is to carry out an analysis of the introduction and functioning of know-how, as well as to determine the vectors of its use, taking into account the needs of participants in legal relations arising in this area. The subject of research – information technologies (know-how) as objects of intellectual property rights in their use. The methodological basis consists of the method of analysis, the method of synthesis, the dialectical method, the comparative-legal method, the system method, and the logical-legal method. The result of this work is to identify the importance of the information technologies in everyday life of modern society and the level of popularity of their use, outlining possible vectors of development in the economics in the direction of digitalization and justification of the need to improve the provisions of current legislation within the considered topic, expressing the idea of the direction of innovative information policy in the direction of active use of blockchain and maximum compliance with the protection of personal data of customers.